Model reference adaptive control on glucose for the treatment of diabetes mellitus - Abdul Rahman, Abdul Wahab; Kong, Y. K.; Quek, Chai (2006)
Diabetes mellitus is one of the top five killer among both man and woman world wide. Type I diabetes is caused by the failure to produce sufficient insulin which leads to an uncontrolled increase in blood glucose. Prolong elevated glucose level of above 150-160mg/dl poses significant health risk with possible long lasting effect. Human assisted insulin injection through compartmental model schedules are basically open loop system. This paper attempts to close the loop by employing model reference adaptive control on a controller to adaptively control the glucose level of the patient via an infusion pump. Simulation results show the potential of using fuzzy type controllers for finer regulation and its practical applications.